Precast segmental reinforced concrete walls under eccentric compressive loading: An experimental study. (15th April 2016) - Hou, Hetao; Ye, Haideng; Qu, Bing; Ma, Tianxiang; Liu, Xiang; Chen, Lei; Zhang, Shuhui
Highlights: PS-RCWs may exhibit different failure modes under eccentric compressive loading. Bonding strength between cast-in-place and precast concrete controls failure mode. PS-RCWs failed due to formation of plastic zones exhibit higher strength. Plane section remains plane in PS-RCWs failed due to formation of plastic zones. A model recommended in GB50010-2012 is valid for calculating strength of PS-RCWs. Abstract: Precast Segmental Reinforced Concrete Walls (PS-RCWs) are construction units recently developed for modern modular construction. A typical PS-RCW is comprised of cast-in-place concrete enclosed by two precast concrete panels. This paper experimentally investigates performance of the PS-RCWs under eccentric compressive loading. Eight specimens including seven PS-RCW specimens and one conventional cast-in-place reinforced concrete wall specimen were tested. Test results show that the bonding strength between the cast-in-place concrete and precast concrete panels controls the failure modes of the PS-RCWs under eccentric compressive loading. It is found that a PS-RCW with sufficient bonding strength between the cast-in-place concrete and precast concrete panels exhibits the more favorable failure mode in which a plastic zone forms in the wall as a result of the eccentric compressive loading. Testing data also revealed that the classic strain and stress diagrams assumed for reinforced concrete members under eccentric compressive loading can be extended to PS-RCWs. An analytical model recommended in the Chinese National Code for Design of Concrete Structures (GB50010-2012) was found to provide reasonable predictions for strength of the PS-RCWs under eccentric compressive loading and it is recommended for future practice.